2022
DOI: 10.3390/molecules27248802
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization of Phytoantioxidant and Photoprotective Compounds from Carob Pods (Ceratonia siliqua L.) Using Ultrasonic Assisted Extraction Method

Abstract: The current study first describes the extraction of phytoantioxidant polyphenols from Carob byproducts (pods) using maceration and heating-assisted extraction as traditional methods and ultrasonic-assisted extraction (UAE) as an innovative method to determine the most efficient extraction process in terms of four targeted responses: total phenolic content (TPC), antioxidant activities (TAC and DPPH), and photoprotective properties as measured by the sun protection factor (SPF). Second, we used response surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 83 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…In the literature, there are many studies comparing different extraction methods to prepare an active extract. The solvent concentration, the extraction time, and the extraction temperature are the parameters that most influence the phytochemical profile of the extracts [ 15 , 35 , 36 ]. Generally, the ethanol–water mixtures have been found to be effective for the antioxidants’ extraction from botanical materials [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are many studies comparing different extraction methods to prepare an active extract. The solvent concentration, the extraction time, and the extraction temperature are the parameters that most influence the phytochemical profile of the extracts [ 15 , 35 , 36 ]. Generally, the ethanol–water mixtures have been found to be effective for the antioxidants’ extraction from botanical materials [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The solvent concentration, the extraction time, and the extraction temperature are the parameters that most influence the phytochemical profile of the extracts [ 15 , 35 , 36 ]. Generally, the ethanol–water mixtures have been found to be effective for the antioxidants’ extraction from botanical materials [ 36 ]. In this study, a C. siliqua pod extract was prepared through sonication and maceration in a 70:30 ( v / v ) ethanol–water mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the aqueous methanolic seed extracts from both Cretan cultivars absorbed more than the hexane seed extracts. A recent study on the effects of processing in ethanolic C. siliqua pod extracts regarding their antioxidant and photoprotective potential [16] included a calculation of in vitro SPF, which ranged from 8.62 to 22.37. In our study, we found lower SPF values, ranging from 2.14 to 3.95, regarding the deseeded pod extracts.…”
Section: Discussionmentioning
confidence: 99%
“…A less studied aspect regards the use of carob in the cosmetic industry, although the polysaccharide galactomannan (locust bean gum or E410) from the seed endosperm is already being used in the cosmetic sector, mainly due to its physical properties [15]. A recent study suggested that carob extracts, beyond their well-known antioxidant properties, also possess photoprotective activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to mature fruits, Ayad et al [41] published a value of 23.375 ± 0.83 mg GAE/g DM in ripe carob pods from the Texenna region in Jijel. Many authors [12,31,34,39] found that the total phenolic content of carob decreased gradually during ripening to the lowest levels at the end of maturity.…”
Section: Quantification Of Bioactive Compoundsmentioning
confidence: 99%